Najiba Mullah Mohammad Jalizadeh Koyi Life and Role in Writing History - Mahmood, Asst.Prof.Dr.Hoshmand Ali Mahmood; Rasoul, L.Dr.Zamdar Ahmad Rasoul (Sulaimani Journal for Humanities, 2026)
Najiba Mullah Mohammad Jalizadeh Koyi (1917- 1999) is one of the most prominent female writers of the last century. She was recognized for her own distinctive perspectives and views that are resulted from the influence of her educated family members that played a great role in the field of education and upbringing. Her writings: Kurdish News (1962-1963), Kurdish News (1961-1962/ 1965-1966), Koya History and Jalizadeh History ware a medium to narrate historical events. These works are of great importance for history and understanding the earlier events and views. From females’ perspectives and views towards history, we can have a feminine understanding of the historical events. In these works, she expresses her thoughts, promotes education and literacy, advises Kurds to have awareness, and encourages women to become influential characters within the events, and get out of the house. Moreover, she played a great role in the development of women’s affairs of her time by going beyond common traditions as she was the first religious man’s daughter to join a boys' school. This study aims at illustrating the ability and role of women in history, understanding female's perspectives about history, and highlighting the status of women and their views on the events. This study draws on the method of narrating historical events, analyzes the summary of Najiba's life, works and writings, and demonstrates her roles in reciting the local history. This research consists of two sections. The first section is devoted to the stages of Najiba Jalizadeh's life, and the second section discusses her works and her role in writing history.
Keywords: Women; Kurdistan; Education; Womens Union; Writing History